Unmet Needs at the Time of Emergency Department Discharge. (13th February 2016) - Samuels‐Kalow, Margaret; Rhodes, Karin; Uspal, Julie; Reyes Smith, Alyssa; Hardy, Emily; Mollen, Cynthia
Abstract: Objectives: Emergency department (ED) discharge requires conveying critical information in a time‐limited and distracting setting. Limited health literacy may put patients at risk of incomplete comprehension, but the relationship between discharge communication needs and health literacy has not been well defined. The goal of this study was to characterize the variation in needs and preferences regarding the ED discharge process by health literacy and identify novel ideas for process improvement from parents and patients. Methods: This was an in‐depth qualitative interview study in two EDs using asthma as a model system for health communication. Adult patients and parents of pediatric patients with an asthma exacerbation and planned discharge were enrolled using purposive sampling to balance across literacy groups at each site. Interviews were audiotaped, transcribed, coded independently by two team members, and analyzed using a modified grounded theory approach. Interviews were conducted until thematic saturation was reached in both literacy groups at each site. Results: In‐depth interviews were completed with 51 participants: 20 adult patients and 31 pediatric parents. The majority of participants identified barriers related to ED providers, such as use of medical terminology, and systems of care, such as absence of protected time for discharge communication. Patients with limited health literacy, but not those with adequate literacy, identified conflicting information between health care sources as a barrier to successful ED discharge. Conclusions: Participants across literacy groups and settings identified multiple actionable areas for improvement in the ED discharge process. These included the use of simplified/lay language, increased visual learning and demonstration, and the desire for complete information. Individuals with limited literacy may particularly benefit from increased attention to consistency.